Unravelling the effect of healing conditions and vulcanizing additives on the healing performance of rubber networks. (3rd January 2022) - Araujo-Morera, Javier; López-Manchado, Miguel A.; Verdejo, R.; Hernández Santana, Marianella
Abstract: Self-healing rubbers have steadily been growing during the last decades. Various strategies have been studied to transform the vulcanized rubber into a reversible cross-linked network with multiple repair cycles. However, a detailed description on how the chemical constituents of a rubber formulation affect the healing properties of the vulcanizate is unknown and has not been reported until now. In this research, the individual effects of both the curing agent (sulfur and peroxide) and the activating complex (zinc oxide and stearic acid) have been assessed on the healing capability of a styrene-butadiene rubber (SBR) compound. The analysis of different healing conditions revealed that pristine materials should be subjected to the same thermal treatment as the healed samples to obtain scientifically sound values of the healing efficiency. Results also showed that each component affected the healing at different time scales, with the activating complex being responsible for the initial physical healing stage. Meanwhile, sulfur would act at later stages as dynamic healing moiety, enabling disulfide exchange reactions. In conclusion, the mechanical recovery of a rubber network can be potentially tailored depending on the relation between the chemical components of the rubber formulation. Graphical abstract: Image 1 Highlights: Vulcanization additives affect the healing capability of a SBR compound. Zinc oxide and stearic acid favor chain entanglements and interdiffusion. Sulfur promotes healing through disulfide exchange reactions. Optimal sulfur content (1 phr) results in a healing efficiency of 80%. SBR compound exhibits a repeatable healing after multiple cycles.